Pulp tissue inflammation and angiogenesis after pulp capping with transforming growth factor β1 - Sri Kunarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
In Restorative dentistry the opportunity to develop biomemitic approaches has been signalled by the possible use of various biological macromolecules in direct pulp capping reparation. The presence of growth factors in dentin matrix and the putative role indicating odontoblast differentiation during embryogenesis has led to the examination on the effect of endogenous TGF-β1. TGF-β1 is one of the Growth Factors that plays an important role in pulp healing. The application of exogenous TGF-β1 in direct pulp capping treatment should be experimented in fibroblast tissue in-vivo to see the responses of inflammatory cells and development of new blood vessels. The increase in food supplies always occurs in the process of inflammation therefore the development of angiogenesis is required to fulfil the requirement. This in-vivo study done on orthodontic patients indicated for premolar extraction between 10–15 years of age. A class V cavity preparation was created in the buccal aspect 1 mm above gingival margin to pulp exposure. The cavity was slowly irrigated with saline solution and dried using a sterile small cotton pellet. The sterile absorbable collagen membrane was applied and soaked in 5 ml TGF-β1. It was covered by a Teflon pledge to separate from Glass Ionomer Cement restoration. Evaluation was performed on day 7; 14; and 21. All samples were histopathologycally examined and data was statistically analysed using one way ANOVA and Dunnet T3.There were no inflammatory symptoms in clinical examination on both Ca(OH)2 and TGF-β1, but they increased the infiltration of inflammatory cells on histopathological examination. There were no significant differences (p > 0.05) between Ca(OH)2 and TGF-β1 in inflammation cell and significant differences (p < 0.05) in angiogenesis on day 7 and 14. There were no significant differences (p > 0.05) in inflammation cell with in TGF-β1 groups and significant differences (p < 0.05) with in Ca(OH)2 groups on day 7 and 14. It is concluded TGF-β1 functions as direct capping medication has the same inflammatory response as Ca(OH)2, however, TGF-β1 developed angiogenesis earlier than Ca(OH)2.